Rekontruktif: Kritik Terhadap Positivisme dalam Filsafat Ilmu dan Relevansinya untuk Perkembangan Studi Administrasi Publik: Reconstructive: Criticism of Positivism in the Philosophy of Science and Its Relevance for the Development of Public Administration Studies - Oktavia, Yelvi; Fitrisia, Azmi; Fatimah, Siti (Undiksha, 2024)
This article aims to explore criticisms of positivism in the philosophy of science and its relevance to the development of public administration science. The study employs a descriptive-qualitative approach through a literature review to investigate the conception of positivism, its criticisms, and its application in public administration. The results indicate that in the context of public administration, the complexity of phenomena cannot be simply reduced by positivist approaches. Therefore, the reconstructive approach emerges as an intriguing alternative, offering a more holistic, interpretative, and critical perspective in understanding phenomena and practices in public administration. The application of the reconstructive approach in public administration studies involves critical analysis of institutions and policies, interpretative case studies, analysis of power and interests, and collaboration among stakeholders in the policy-making and implementation processes.